CHILD HEADACHE: MODERN CLASSIFICATION, CLINICAL DETAILS, TREATMENT ISSUES - E.I. Karpovich ("Paediatrician" Publishers LLC, 2008)
The article is devoted to classification, diagnostics and treatment of headaches. It describes positive properties of ibuprofen which is recommended for relieving pain for children as young as 3 months old. Key words: children, headache, classification, diagnostics, treatment.